FALSAFAH BANGSA DAN BUDAYA JAWA DALAM PEMIKIRAN SOEHARTO - Yusuf Wibisono (Universitas Nasional, 2020)
Soeharto's thoughts in the repertoire of Indonesian political thought tend not to be found much, however, as President of the Republic of Indonesia for approximately 32 years, Suharto has instilled an economic and political foundation in Indonesia that cannot be separated from the current conditions. The policies and political decisions Soeharto took were influenced by the political culture that lay behind his personal life. Political socialization that developed into a political culture in Soeharto was seen in his political struggle leading to the construction of a feudalistic political system, thus influencing Indonesia's political culture. As a leader, Suharto understood what was tried and thought for the nation and the survival of its people, all of which were extracted from Javanese cultural thinking. This all resulted from how he could adapt Javanese cultural thinking which incidentally contained a philosophy of prosperity and national welfare.